(untitled) (Praxis Educativa, 2012)
The article shows some reflections on the incorporation of information and communication technologies (ICT) in the official education policies schedule and in teacher training from the 90’s decade until now. Some investigations’ criteria and concepts which thought around teachers training in ICT, is given first. The official actions and programs around ICT’s teaching incorporation are later described. Finally, we have done a critical analysis during ICT’s incorporation on schools as regards the impact, transformation and innovation on the education system.